The role of floods on pathogen dispersion - Bett, Bernard K.; Tumusiime, Dan; Lindahl, Johanna F.; Roesel, Kristina; Grace, Delia (Springer, 2021)
Floods precipitate many infectious disease epidemics in humans and animals. These incidences are more prevalent in developing countries where about 80% of illnesses and deaths in humans are water related. This chapter identifies three categories of flood-borne infections based on how floods influence their occurrence patterns. The first category includes acute infections such as cholera and leptospirosis, caused by bacteria that are carried mechanically by water and are often ingested with water or food. These infections thrive in areas with high human population densities with poor sanitation. In these settings, floods enhance transmission of infectious agents between hosts. The second category is vector-borne infections such as malaria, Rift Valley fever, and schistosomiasis. They are transmitted by vectors that breed in inundated areas. Their epidemics often follow flood events by weeks or months depending on the duration of their development cycles. The last category is skin and eye infections that occur following direct contact with contaminated water. All these diseases can be controlled more effectively if the standard surveillance and control measures are integrated with nature-based solutions (NBS) for flood management. Examples the NBS that can be used include re-forestation, tree planting especially along streams, and development of green infrastructure in cities to enhance water retention, infiltration, and replenishment of groundwater.